The Robot Revolution: Managerial and Employment Consequences for Firms - Dixon, Jay; Hong, Bryan; Wu, Lynn (Management Science, 2021)
As a new general-purpose technology, robots have the potential to radically transform employment and organizations. In contrast to prior studies that predict dramatic employment declines, we find that investments in robotics are associated with increases in total firm employment but decreases in the total number of managers. Similarly, we find that robots are associated with an increase in the span of control for supervisors remaining within the organization. We also provide evidence that robot adoption is not motivated by the desire to reduce labor costs but is instead related to improving product and service quality. Our findings are consistent with the notion that robots reduce variance in production processes, diminishing the need for managers to monitor worker activities to ensure production quality. As additional evidence, we also find that robot investments predict improved performance measurement and increased adoption of incentive pay based on individual employee performance. With respect to changes in skill composition within the organization, robots predict decreases in employment for middle-skilled workers but increases in employment for low- and high-skilled workers. We also find that robots predict not only changes in employment but also corresponding adaptations in organizational structure. Robot investments are associated with both centralization and decentralization of decision-making authority depending on the task, but decision rights in either case are reassigned away from the managerial level of the hierarchy. Overall, our results suggest that robots have distinct and profound effects on employment and organizations that require fundamental changes in firm practices and organizational design. This paper was accepted by Lamar Pierce, organizations.